The Role of Social Work in Promoting Occupational Health and Safety Awareness among Sawmill Workers in Benin City - Uwagbale, Raymond Francis; Omorogiuwa, Trace B.E. (NIU Journal of Social Sciences, 2025)
Globally and in Africa, including Nigeria, sawmill workers continue to operate under dangerous conditions that expose them to injuries, respiratory complications, and musculoskeletal disorders. Such risks are often linked to unsafe environments, poor adherence to safety standards, and inadequate protective gear, making it urgent to strengthen training, enforcement, and social work programmes aimed at building safety consciousness. This research examines how social work efforts influence occupational health and safety awareness among sawmill workers in Benin City, considering the socio-cultural norms that shape their behaviours, attitudes, and sense of risk. Drawing on Social Cognitive Theory, which emphasises the influence of peer and supervisor role modelling on behaviour, and Organisational Behavioural Theory, which attributes safety failures to weak awareness, ineffective leadership, and unsupportive workplace cultures, the study argues that purposeful social work involvement, training, and institutional support can foster safer routines. Using a descriptive design, data were gathered from 480 sawmill workers selected through purposive, cluster, and quota sampling methods, with a reliable and validated questionnaire and ethical safeguards in place. Results show that most of these workers are young men with minimal formal education who generally follow safety rules, yet lingering hazards remain. Although social work efforts have improved compliance and knowledge, they have had little effect on deeper safety culture or reporting habits, pointing to the need for ongoing education, tighter enforcement, and institutional backing. Consequently, the study recommends regular training, stronger social work engagement, consistent provision of PPE, better monitoring and compliance systems, and greater organisational support to maintain safe working conditions. Keywords: Occupational, Awareness, Health, Hazards, Sawmill workers, Social Work Intervention,